THERMAL MODELING OF THE UHP MAKSYUTOV COMPLEX IN THE SOUTH URALS - Leech M.L.; Willingshofer E. (My University, 2004)
Two-dimensional thermal modeling of the subduction and exhumation of the ultrahigh-pressure (UHP) Maksyutov Complex in the south Ural Mountains tests factors influencing the low modern heat flow in the Urals and the feeble preservation of UHP index minerals. Best-fit models are obtained with initial surface heat flow of 60 mW m À2 indicating that low modern heat flow in the Urals is a recent anomaly. Ultrahigh-pressure metamorphism was modeled at 388 Ma based on new U–Pb SHRIMP dating of zircon; the average modeled exhumation rate for the UHP eclogites to the mid-crust is ~5.0 mm/year, much slower than other UHP complexes. The model predicts that cooling during exhumation is strongly dependent on concomitant subduction/underthrusting in the footwall of the UHP unit and normal faulting in the hanging wall. Low radiogenic heat production in the crust and a relatively thin UHP slab (3–10 km) also favor cooling. For Maksyutov, the modeling shows that cooling was controlled by low radiogenic heat production and underthrusting during decompression to lower crustal levels; these cooling mechanisms accompany exhumation despite low exhumation rates (~5 mm/year) thereby denying the call for fast exhumation in order to preserve UHP index minerals.